2015
DOI: 10.1177/0892705715610407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recycling on polypropylene composites reinforced with glass fibres

Abstract: The aim of the work was to investigate the effect of recycling on the mechanical behaviour of polypropylene composites reinforced with glass fibres (GFs), starting from a material already used in automotive for vehicle components, obtained by injection moulding. Formerly specimens of pristine composites were subjected to tensile and flexural tests, then the specimens were grinded, reprocessed and recycled only once. The recycled composites showed a slight decrease in the elastic modulus and tensile and flexura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…The influence of these individual processes is not determined in this study. However, according to the Colucci et al (2017), the reduction is mainly caused by the mechanical recycling process. After ten consecutive recycling and injection molding steps, the fiber length reduction has even further increased as there is a very high frequency (> 75 %) of small fibers (< 100 µm).…”
Section: Effect Of Recycling On the Fiber Length Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of these individual processes is not determined in this study. However, according to the Colucci et al (2017), the reduction is mainly caused by the mechanical recycling process. After ten consecutive recycling and injection molding steps, the fiber length reduction has even further increased as there is a very high frequency (> 75 %) of small fibers (< 100 µm).…”
Section: Effect Of Recycling On the Fiber Length Distributionmentioning
confidence: 99%
“…These studies have shown that the tensile modulus, tensile strength, flexural modulus and flexural strength of the recycled material decrease compared to the virgin material. In contrast, the tensile strain at break and impact strength of the recycled material increase (Bernasconi et al, 2007;Bourmaud and Baley, 2007;Colucci et al, 2017;Giraldi et al, 2004;Kuram et al, 2014;Kuram et al, 2016). During all these experiments, a maximum of five recycling steps were executed.…”
mentioning
confidence: 99%
“…Short glass fiber-reinforced polypropylene (GFRPP) composites are recyclable materials with good mechanical properties, high chemical resistance, excellent thermal stability, and attractive performance-cost ratio. In view of these advantages, the GFRPP is widely used in structural applications in the fields of aerospace, automotive, civil, and marine engineering [1][2][3][4][5]. It is well known that the macroscopic performance of the product is substantially dependent on its microstructure [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, for the PP/hemp with 30 wt%, these properties vary only by +1.81%, -0.66% and +22.3%, respectively. Moreover, Colucci et al [10] studied the effect of mechanical recycling on glass fibre reinforced polypropylene composite. As a result, they noticed that after one mechanical recycling cycle, their mechanical properties decrease by 8.5%, 23.8% and 27.5% for Young's modulus, tensile strength and flexural strength, respectively, with respect to the values of non-recycled material.…”
Section: Introductionmentioning
confidence: 99%